Effect Of Supervision And Work Discipline To Employee Performance High Prosecutor Of Kabupaten Kaur - Suhendar, Cecep; Irwanto , Tito; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to determine the effect of supervision and disciplinary work on the performance of Kaur Regency High Prosecutor's Office employees. The population in this study was all 29 employees of the Kaur Regency High Prosecutor's Office, with a total sample of 29 employees. The sampling technique is cluster sampling. Data analysis technique using multiple linear regression. The research results show that by simultaneously comparing the Fcount value with Ftable, it is known that the Ftable value is 3.757 > 3.16 and it can be concluded that supervision and work discipline have a significant effect on employee performance at the Kaur District District Prosecutor's Office. Based on the partial test, it is known that supervision has a positive and significant effect on the performance of the Kaur Regency District Prosecutor's Office employees with a sig value of 0.004 < alpha (0.05), while work discipline has a positive and insignificant effect on the performance of the Kaur Regency District Prosecutor's Office with a sig value of 0.810 > alpha (0.05)